PENINGKATAN KEMAMPUAN LITERASI DASAR MELALUI METODE MEMBACA TANPA MENGEJA DI KELAS 1 MI SUNAN GIRI NGAMPEL NGUSIKAN JOMBANG - Khoirun Nisya, Miftahul Aulia; Mahsun, Ali (Discovery : Jurnal Ilmu Pengetahuan, 2023)
Based on initial observations, there is a problem that at the beginning of each new school year, there are students in class 1 who cannot read, while a lot of the material in class 1 has a lot of story text material and is linked to questions. Therefore, students are instructed to answer questions from the story text they read. To make it easier to read fluently, methods are needed that are linked to the subjects in class. This research aims to describe the improvement of basic literacy skills through the method of reading without spelling in class 1 at MI Sunan Giri Ngampel Ngusikan Jombang. Researchers obtain data using observation, interviews, documentation. The research subjects were grade 1 students at MI Sunan Giri Ngampel Ngusikan Jombang. Data analysis techniques, data reduction, data presentation, drawing conclusions and verification. The data validity checking technique uses triangulation of sources and techniques. In its implementation, students sit facing the teacher and are invited to recognize letters so that they can read words and sentences and can write answers to the reading texts in the worksheet. The implementation is Monday, Tuesday, Friday and Saturday. For evaluation, use an achievement book, in the book there are columns for day, date, level read, page, score 90-100 reading fluently, 80-89 stammering, 70-79 not yet fluent and teacher's initials. So by implementing the method of reading without spelling continuously and having achievement books for grading, it will improve the basic literacy skills of students in class 1, especially those who cannot yet read.